Perception of university students about doctors and quality of health care provision at clinics: a multi-national study in India, Pakistan, Spain and United States of America - Limaye, Dnyanesh; Fortwengel, Gerhard; Pitani, Ravi Shankar; Sathe, Sushama; Chivate, Sanika; Jagadale, Prabhas; Saeed, Farah; Alam, Syed Mahboob; Rodilla, Vicent; Mounib, Chaimae; Jr., Edel Santiesteban (International Journal of Research in Medical Sciences, 2019)
Background: Patient satisfaction is considered as an indicator of the healthcare quality. Information on patient satisfaction based on medical expertise of the physician, interpersonal skills, physician-patient interaction time, perception and needs of the patient allow policymakers to identify areas for improvement. Primary care services and healthcare structure differ between the countries. The present study was done to determine and analyze the determinants associated with patient satisfaction in India, Pakistan, Spain and USA. Methods: This descriptive study was performed in January to August 2019 among students from Mumbai University, India, Dow University of Health Sciences, Karachi, Pakistan, University CEU Cardenal Herrera, Valencia, Spain, Texas State University, Texas, USA. On the basis of the eligibility criterion (those who gave a written informed consent and were registered students of respective university) 890 (India: 369, Pakistan: 128, Spain: 195, USA: 99) students were selected for the present study. Results: India had almost similar male (49%) to female (51%) ratio of participants. For other 3 countries (PK, ES, US), female participant percentage was nearly 20% or even more as compared to male participants. Overall participant’s satisfaction score about medial expertise of the doctor were highest in India (71%) and were lowest in Spain (43%). Overall satisfaction score about time spent with doctor were highest for India (64%) and were lowest for Spain (41%). Overall satisfaction score about communication with doctor were highest for US (60%) and were lowest for PK (53%). Overall satisfaction score for medical care given by the doctor was lowest in PK (43%) and was highest in US (64%). Overall satisfaction about doctor, highest number of US (83%) and lowest number of PK (32%) participants were satisfied about medical interaction with doctors. Conclusions: These multi-country findings can provide information for health policy making in India, Pakistan, Spain and USA. Although the average satisfaction per country, except Pakistan is more than 60%, the results suggest that there is ample room for improvement.